The Effect of Plasma Fibrinogen Levels on Measures of Fibrinolytic Activity - Chakrabarti, R; North, W R S; Meade, T W (Thrombosis and Haemostasis, 1978)
It has been claimed that lysis time methods may be inappropriate as measures of fibrinolytic activity on the grounds that they are largely determined by plasma fibrinogen levels. The dilute blood clot lysis time (DBCLT) has therefore been measured in 103 subjects; fibrinolytic activity (expressed as 100/DBCLT) has been compared with the fibrin plate area (FPA) lysed by the euglobulin fraction, the latter method being, of course, virtually independent of plasma fibrinogen. Plasma fibrinogen levels have also been measured; they ranged from 167 to 416 mg%. Results have been analysed by the technique of multiple regression. The incorporation of plasma fibrinogen levels in the regression equation relating 100/DBCLT to FPA does not result in a significant increase in the proportion of the variance in 100/DBCLT that can be explained. It is concluded that there is no evidence that DBCLT is influenced by plasma fibrinogen levels within the physiological range.